Analysis Management Of Mosque Taqwa Contribution In Assisting Revenue Jamaah To Members Muhammadiyah In Medan - Selamat Pohan; Frida Yanti Sirait (Proceeding International Seminar of Islamic Studies, 2019)
The mosque is used as a means of fostering , as well as a center for community activities in a positive and productive manner . Included in this case the mosque became the center of economic development . The purpose implementation of research this is to provide supplies conceptual and practical to citizens Muhammadiyah on Management Mosque Taqwa Contribution in Assisting Jamaah Revenue for Muhammadiyah Members in Medan City. Results of the study show , based on the analysis of the findings that there is that Contributions Masjid Taqwa Muhammadiyah in Helping Revenue Jamaat to Members Muhammadiyah In Medan has not been implemented with good . Reasons were obtained by researchers such , that the mosque Taqwa Muhammadiyah do not have program budget for special programs such . Even if there is a type of assistance that has been carried out by one of the officials of the Taqwa Mosque due to the incident factor of the management's policies . It is in pointed out by one of the Nara source that has researchers encountered . And the findings have reinforced the opinion of one of the members of Muhammadiyah who is also active as a congregation in the neighborhood Masjid Taqwa Muhammadiyah . Then, based on the data interviews that the researcher did on Contributions Masjid Taqwa Muhammadiyah in Helping Revenue Jamaah , researchers can conclude that the Management Masjid Taqwa Muhammadiyah has not apllied the program